ECONOMICS OF PIG-FISH INTEGRATED FARMING IN KOKRAJHAR DISTRICT OF ASSAM (Indian Journal of Animal Production and Management, 2014)
An investigation was undertaken under NAIP (Component – 3) sub project with 40 farm households for evaluation of small scale farm economics under integrated farming system in Kokrajhar district of Assam. Farmers were provided with 2 local female and one Hampshire male piglets of two months old. Fish species like catla, rohu, mrigal, grass carp and silver carp were released in the ponds @8,888 per ha. Semi permanent pig-sty on pond embankment with floor of the pig-sty designed in such a way that sludge flow to the fish pond during washing and cleaning. The fishes did not receive any extra feed and fish pond did not receive any extraneous fertilizers. Pig sludge is recycled to produce table fish. The pig (Hampshire) was introduced as for crossing with local female pig as an integral component of the pig-fish farming system. An average of 2.17±0.75 quintal of fish was produced after one year in a pond area of 450 m2 which was lacking in traditional practices. The study indicated that integrated farming system was found much better over traditional system when benefit cost ratio (BCR) was calculated to be 3.2:1 vs 1.4:1 respectively. Another significant additional source of income was that the non-beneficiary farm families in the project sites were hiring the service of the male Hampshire pigs provided under the NAIP project with a precondition that one piglet borne out of the total would be given to the owner of the male who is a beneficiary farmer of the NAIP in the mode of payment in kind for the service by his male pig. Thus two distinct benefits are accrued- there is a continuous horizontal extension through pig breed improvement activity and additional income generation for the farm families of the NAIP sub- project.
Keywords: Integrated farming system; pig-fish; economics; benefit cost ratio